The Effect of Brand Image, Product Quality, and Price Perception on Erspo Jersey Purchasing Decisions - Effendi, Stefanus Dhani; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purpose of this study is to partially and concurrently assessing how perceptions of pricing, product quality, and brand image affect decisions to buy Erspo jersey. Design/Method/Approach : This study employs a causality technique in a quantitative manner. 40 respondents' responses to a standardized questionnaire using a Likert scale were gathered. Validity, reliability, multiple linear regression analysis, classical assumptions, and the t and F experiments using SPSS version 23 are examples of data analysis approaches. Research Finding : The findings demonstrated that while brand image has no discernible outcome on purchase decisions, perceptions of product quality and price had a major outcome. With a combined contribution of 71.4% (R²), the three independent factors significantly impact purchase choices. Theoretical contribution/Originality : This study supports the idea that the primary determinants of purchase decisions are perceived product quality and price. The study's uniqueness is in its concurrent examination of pricing perception, product quality, and brand image in relation to regional brands in Indonesia's developing sportswear market. Practitionel/Policy implication : This research provides guidance for local brands like Erspo to focus on improving product quality and competitive pricing strategies. This policy can increase the competitiveness of local brands in a market dominated by international products. In addition, the research results can be used as a reference for the government and business actors to support the development of local brands. Research limitation : This study is limited to a small sample size and narrow geographical coverage. Future research agendas suggest expanding the sample coverage and adding other variables, such as the influence of social media or celebrity endorsement, to understand more complex factors in purchasing decisions.